Amazinger Face : clever beauty tricks, should-own products, spectacularly useful how-to-do-its - Foster, Zoë, 1980-; Penguin Random House Australia (Australia : Viking, an imprint of Penguin Books, 2016)
Sometimes a lady just needs to know the most flattering lipstick for her skin tone, or how to correctly use sunscreen, or a very quick hairstyle to conceal her unwashed hair. And there's no reason she shouldn't know which foundation or mascara is best for her, either. All the answers are here, in this top-to-toe beauty extravaganza. Former Cosmopolitan and Harper's BAZAAR beauty director, and the founder of Go-To skin care, Zoë Foster (Blake) suggests makeup colours and brands for every occasion, useful, practical skin care routines and products for every age, and step-by-step instructions for winged eyeliner, arresting red lips, foolproof tanning, simple up-dos, sexy second-day hair, and much, much more . . .
At head of title: "Fully revised and updated! Over 60 new pages! New longer title!"
Includes index.
General.
Keywords: Beauty, Personal; Cosmetics; Beauty, Personal; cosmetics; Cosmetics; Electronic books